Being kind in unkind spaces: a qualitative examination of how medical educators and first year medical students perceive empathy training - Harvey, Sarah D. C.; Stacey, Clare L. (Frontiers in Sociology, 2024)
Introduction It has become de rigueur for healthcare systems to tout their ability to provide compassionate medical care that addresses the emotional as well as physical needs of patients. Not surprisingly, then, there is considerable pressure on medical schools to train their students to be empathic. Existing literature on empathy training in medicine tends to focus on how to build emotional intelligence in individual trainees, largely ignoring the sociocultural factors that contribute to or thwart empathy development in medical school. Additionally, research tends to examine student perspectives, with little attention given to medical educators and their viewpoints. Methods In this paper, we adopt an “emotion practice” framework and utilize an inductive descriptive study design to qualitatively consider how first year medical students (N = 23) and their instructors (N = 9) perceive empathy training at a site we call Midtown Medical School. Results and discussion We find that both groups have an understanding of empathic capital but differ in their beliefs about the utility and legitimacy of this capital. Both educators and students also recognize the limitations of standardized empathy curriculum but do not agree on the implications of such rote learning. Finally, students and instructors alike find the hidden curriculum of medical school to be antithetical to empathy development, concurring that it is difficult to cultivate empathy in spaces where biomedical coursework is prioritized over social–emotional learning. In short, both groups find it difficult to be kind in an unkind place.